Influence of platelet-activating factor receptor (PAFR) on Brucella abortus infection: implications for manipulating the phagocytic strategy of B. abortus. Issue 1 (December 2016) - Lee, Jin; Simborio, Hannah; Reyes, Alisha; Hop, Huynh; Arayan, Lauren; Lee, Hu; Min, Wongi; Her, Moon; Rhee, Man; Watarai, Masahisa; Chang, Hong; Kim, Suk
Abstract Background Brucella abortus is an intracellular pathogen which can infect and persist in host cells through multiple interactions. Above all, its interaction to host cell receptor is important to understand the pathogenic mechanisms ofB. abortus . Accordingly, we demonstrated that platelet-activating factor receptor (PAFR) affects host cell response againstB. abortus infection. Results First of all, B. abortus infection to macrophage induces secretion of platelet-activating factor (PAF), which is a PAFR agonist. The stimulation of PAFR by PAF remarkably increasesB. abortus uptake into macrophages. It induces Janus kinase 2 (JAK2) and p38α phosphorylation, indicating that PAFR-mediated activation of JAK2 signaling leads to enhanced uptake ofB. abortus . Moreover, the dynamics of F-actin polymerization revealed that PAFR-mediatedB. abortus uptake is related with the reorganization of F-actin and JAK2. UponB. abortus phagocytosis, reduced PAFR in the membrane and subsequently increased levels of PAFR colocalization with endosomes were observed which indicate thatB. abortus uptake into macrophages allowed PAFR trafficking to endosomes. Conclusions This study demonstrated that PAFR has a compelling involvement inB. abortus uptake as a promoter of phagocytosis, which is associated with JAK2 activation. Thus, our findings establish a novel insight into a receptor-related phagocytic mechanism ofB. abortus .